A systematic review and meta-analysis of cognitive and behavioral interventions to improve sleep health in adults without sleep disorders. (August 2018) - Murawski, Beatrice; Wade, Levi; Plotnikoff, Ronald C.; Lubans, David R.; Duncan, Mitch J.
Summary: Many adults without a diagnosed sleep disorder report poor sleep health, which is defined by dissatisfactory levels of sleep duration, sleep quality, or the timing of sleep. No previous review has summarized and described interventions targeting poor sleep health in this population. This meta-analysis aimed to quantify the efficacy of behavioral and cognitive sleep interventions in adults with poor sleep health, who do not have a sleep disorder. Electronic databases (Medline, Embase, PsycInfo, Cinahl) were searched with restrictions for age (18–64 y) and English language full-text, resulting in 18, 009 records being screened and 592 full-texts being assessed. Eleven studies met inclusion criteria, seven of which reported a measure of overall sleep health (Pittsburgh sleep quality index [PSQI]). Following appraisal for risk of bias, extracted data were meta-analyzed using random-effects models. Meta-analyses showed interventions had a medium effect on sleep quality (Hedge's g  = −0.54, [95% confidence interval (CI)] −0.90 to −0.19, p  < 0.01). Baseline sleep health was the only significant effect moderator ( p  = 0.01). The most frequently used intervention components were stress management and relaxation practice, stimulus control, sleep hygiene, and exercise. Interventions targeting cognitive and behavioral self-regulation improve sleep quality in adults without clinical sleep disorder.